Komunikasi Interpersonal Pengawas Minum Obat Berperspektif Gender dengan Kepatuhan Berobat Penderita Tuberkulosis di Tiga Puskesmas di Kabupaten Bogor - Widiawati Walangadi; Dwi Sadono; Djoko Susanto (Institut Pertanian Bogor, 2017)
The problem of tuberculosis (TB) control is still very large in Indonesia. Pengawas minum obat (PMO) for each patient tuberculosis expected to ensure the regularity of the patients taking medicine. The objectives of the study are 1) to analyze interpersonal communication skills of PMO gender perspective with TB patient, and 2) to analyze relationship between interpersonal communication skills PMO gender perspective with TB patient treatment compliance. Explanatory research method with cross-sectional study design, with a total sample of 82 of the PMO at three Public Health Centers PMO Ciomas, Cileungsi, Cibinong. Data were collected using questionnaire and analyzed using chi-square. The results showed the relationship between the characteristics of the PMO with interpersonal communication skills PMO value of p > 0.01 so give no significant relationship, the relationship between gender perspectif with interpersonal communication skills PMO is p <0.01 means that there is significant correlation. The relationship between the PMO interpersonal communication skills with patient compliance level p <0.01 means that there is a significant relationship. Conclusion characteristics of the PMO are the largely nonexistent relationship with interpersonal communication skills of PMO, whereas the gender perspective is significally correlated to interpersonal communication skills of the PMO. The level of interpersonal communication skills are significantly correlated of TB treatment compliance.